ANÁLISE DA CAMADA NITROCEMENTADA NO AÇO AISI 316 POR MEIO DA TÉCNICA DE FOTOACÚSTICA DE CÉLULA ABERTA - Oyarzabal, Ricardo Sovek (2012)
The photoacoustic technique is a method used in the study of physical and thermal properties of solids, liquids or gases and it is based on the photothermal effect. The photothermal effect results from the combination of physical mechanisms such as thermal expansion, thermal diffusion and thermoelastic bending. Thermal diffusivity is a parameter that measures how much heat is diffused over a sample and depends on the thermal conductivity k, density ρ and specific heat c of the material under analysis. For this study, we used the open cell photoacoustic (OPC) technique to measure the thermal diffusivity of samples of AISI 316 steel. The standard sample has a thickness of 490 micron and a diameter of 31.73 mm as the others received coatings by plasma treatment nitrocarburizing. This process of ion implantation modifies the tribological properties and mechanical characteristics of the region around the surface of a material, as different precipitates are formed, thus changing the thermal diffusivity. In this investigation we divided the samples into three distinct regions, and the area A in the center, an intermediate region B and C is the region most extreme. The theoretical value of diffusivity for the steel AISI 316 is 4.05 x10-6 m2/s. Through the OPC technique the results for each region were: αA = 4.08 x10-6 ± 0,18 m2/s, αB = 4.09 x 10-6 ± 0,12 m2/s , αC = 4.09 x 10-6 ± 0,22 m2/s. These results are close to theoretical values and show that the thermal diffusivity does not radially change from the center to the edge of the sample. For the nitrocarburized samples with circular, circular center hole, triangular and square geometries it was observed, by optical microscopy and thermal diffusivity determination, that the nitrocarburizing is not uniform across the surface of the sample and varies according to its region, with greater intensity at the edges than the center. Thus, OPC is a technique sensitive to the structural changes at surfaces of a bulk so that can be used to distinguish surfaces that have suffered or not nitrocarburizin.